Carbapenemases Produced by Multidrug-Resistant Strains of Klebsiella Pneumoniae Isolated from Intensive Care Patients - T. V. Chernenkaya; L. A. Borisova; T. Yu. Vorobieva; M. A. Godkov; A. K. Shabanov (Неотложная медицинская помощь, 2024)
Relevance Klebsiella pneumoniae is one of the main pathogens of nosocomial infections. Hospital strains of this pathogen are characterized by a high frequency of resistance to many antibiotics, including carbapenems. The main mechanism for the formation of resistance to carbapenems is the production of carbapenemases by bacteria. To date, K. pneumoniae is considered one of the main “distributors” of clinically important antibiotic resistance genes.Aim of the study To study the frequency of occurrence of the most common carbapenemase genes in multiresistant K.pneumoniae strains isolated from patients of intensive care units in an emergency hospital.Material and methods 4708 samples of various types of clinical material from patients of 5 intensive care units of the N.V. Sklifosovsky Research Institute for Emergency Medicine were analyzed. Microbiological studies were carried out using standard generally accepted methods. For the purposes of this study, unique sequential K.pneumoniae strains resistant to imipenem and/or meropenem were selected. DNA isolation was carried out using the RIBO-prep kit (Russia). Carbapenemase genes were detected by real-time PCR using the kits of reagents “AmpliSens MDR-MBL-FL” and “AmpliSens MDR-KPC/OXA-48-FL” on a “Rotor Gene” device (Corbett Research, Australia).Results Etiologically significant microorganisms were detected in 64.7% of the studied samples. K. pneumoniae was isolated in a quarter of the samples. 194 unique carbapenem-resistant strains of K.pneumoniae were selected. Of these, 11.3% of the genes of the studied carbapenemases were not detected. In 38.1% of strains, 1 carbapenemase was detected, in 29.9% — two and in 20.6% — three or more. Among the strains with one carbapenemase gene, OXA-48 (19.1%) and CATTLE (13.4%) producers prevailed. Strains producing only NDM betalactamase were found in 5.7% of cases. Isolated allocation of VIM and IMP was not detected. In 34%, metallobectalamases were isolated in combination with serine carbapenemases. The production of serine carbapenemases alone was detected in 48.5% of the strains. Depending on the specialization of the intensive care unit, there are differences in the frequency of detection of serine and metallobetalactamases in strains of carbapenem-resistant Klebsiella.Conclusion K. pneumoniae is the causative agent of nosocomial infections in 25% of cases. In 11.3% of carbapenem-resistant strains, the production of KPC, OXA-48, NDM, VIM and IMP genes was not detected. When developing algorithms for antibacterial therapy, it is necessary to take into account that from 25.7% to 60.6% of K. pneumoniae strains in different intensive care units are the producers of metallobetalactamases.